HUBUNGAN KOMPETENSI GURU TERHADAP PENGELOLAAN LINGKUNGAN BELAJAR DI RA KECAMATAN TAMPAN PEKANBARU - Rahmah; Roza Yuliawati (P3M STKIP 'Aisyiyah Riau, 2017)
Competence is a basic characteristic of a person that is interrelated with an effective criterion and / or a person's best skills at work. Management of the learning environment is a teacher activity that is related to the arrangement of students, tools, space, and time where the learning process takes place. This study aims to determine the relationship of teacher competence to the management of the learning environment in RA Tampan District, Pekanbaru. The research site was in RA Tampan Subdistrict, Pekanbaru City and the time of this research was conducted from February to April 2016. This research used the correlation method. The population and research sample studied were 44 RA teachers who had not been certified in the Tampan District, Pekanbarus. To obtain this research data used a questionnaire. Techniques to analyze research data using the formula r Product Moment. The results showed the results of this study showed a significant relationship between teacher competence and management of the learning environment in RA Tampan District, Pekanbaru. This means that the competence possessed by the teacher really affects the management of the learning environment, in other words, the better the management of the learning environment in RA, Tampan District, Pekanbaru. This can be seen from the calculated F value of 26.535> F table 4.06.